Effectiveness of a modified Balint group process on empathy and psychological skills employing Kirkpatrick’s evaluation framework - Antoun,Jumana; Khater,Beatrice; Itani,Hala; Naous,Jihane; Romani,Maya (PeerJ, 2023)
Background To evaluate, using Kirkpatrick’s evaluation model, a modified Balint group (BG) by adding 5–10 min at the end of the session, where the facilitators will debrief the residents about critical themes mentioned in the session. Methods A quasi-experimental study with a mixed-method design was conducted among family medicine residents over 1 year, using focus groups and validated tools filled by residents and their corresponding patients. The residents’ empathy through self and patient evaluation, psychological skills, and satisfaction with the educational activity were measured. Results The focus group revealed that the residents were aware of the change and considered it a closure to the encounter, helping decrease some uncertainty. Most of the residents did not consider the change helpful. Using validated instruments, BG was ineffective at improving the residents’ empathy and psychological skills. There was a statistically significant main effect of time on Psychological Medicine Inventory (PMI) scores, F (1,13) = 7.709, p = 0.016. Conclusion Debriefing at the end of BG by the facilitators about key themes may help give the residents closure, decrease the uncertainty, and make them more aware of their feelings. Nevertheless, Balint groups are still not very well accepted by the residents, and they prefer direct feedback and support groups.
Keywords: Balint; Empathy; Post-graduate training; Family medicine